Global sourcing processes in the Italian agricultural breweries. Issue 10 (15th August 2019) - Francioni, Barbara; Curina, Ilaria; Masili, Giorgia; Viganò, Elena
Abstract : Purpose: The purpose of this paper is to deepen the global sourcing (GS) phenomenon from the acquiring firms' viewpoint by analyzing the Italian craft beer sector. This industry has been chosen since it represents a perfect context for the GS activities' analysis. Notably, different features characterizing this business force Italian breweries to turn to suppliers, located outside their national borders, to purchase the necessary raw materials. Design/methodology/approach: The paper adopts a multiple case study concerning four Italian agricultural breweries located in the Marche region. Findings: Results identify the main motivations, drivers, risks, obstacles and costs related to the adoption of the GS activities, by corroborating a positive interconnection with the GS literature findings. Research limitations/implications: The main limitation is related to the fact that the study is based on a survey carried out on a specific region and product category. Therefore, future research could analyze other Italian regions and/or different types of products. Practical implications: The study identifies different gaps characterizing the Italian supply market. Managerially these gaps can be converted into critical opportunities for the future development of the entire Italian brewing sector. Moreover, the results detect several actions the investigated breweries will seek to develop in the near future, which could strongly support the growth of the Italian beer sector. Originality/value: The study deepens a topic little explored by literature, especially with reference to the supply activities of the Italian agricultural breweries.